Activation of β- and γ-carbonic anhydrases from pathogenic bacteria with tripeptides - Stefanucci, Azzurra (J Enzyme Inhib Med Chem, 2018)
Six tripeptides incorporating acidic amino acid residues were prepared for investigation as activators of β- and γ-carbonic anhydrases (CAs, EC 4.2.1.1) from the pathogenic bacteria Vibrio cholerae, Mycobacterium tuberculosis, and Burkholderia pseudomallei. The primary amino acid residues that are involved in the catalytic mechanisms of these CA classes are poorly understood, although glutamic acid residues near the active site appear to be involved. The tripeptides that contain Glu or Asp residues can effectively activate VchCAβ and VchCAγ (enzymes from V. cholerae), Rv3273 CA (mtCA3, a β-CA from M. tuberculosis) and BpsCAγ (γ-CA from B. pseudomallei) at 0.21–18.1 µM levels. The position of the acidic residues in the peptide sequences can significantly affect bioactivity. For three of the enzymes, tripeptides were identified that are more effective activators than both l-Glu and l-Asp. The tripeptides are also relatively selective because they do not activate prototypical α-CAs (human carbonic anhydrases I and II). Because the role of CA activators in the pathogenicity and life cycles of these infectious bacteria are poorly understood, this study provides new molecular probes to explore such processes.